Temperature regulates deterministic processes and the succession of microbial interactions in anaerobic digestion process - Lin, Qiang; De Vrieze, Jo; Li, Chaonan; Li, Jiaying; Li, Jiabao; Yao, Minjie; Hedenec, Petr; Li, Huan; Li, Tongtong; Rui, Junpeng; Frouz, Jan; Li, Xiangzhen (Water research, 2017)
Temperature plays crucial roles in microbial interactions that affect the stability and performance of anaerobic digestion. In this study, the microbial interactions and their succession in the anaerobic digestion process were investigated at three levels, represented by (1) present and (2) active micro-organisms, and (3) gene expressions under a temperature gradient from 25 to 55 °C. Network topological features indicated a global variation in microbial interactions at different temperatures. The variations of microbial interactions in terms of network modularity and deterministic processes based on topological features, corresponded well with the variations of methane productions, but not with temperatures. A common successional pattern of microbial interactions was observed at different temperatures, which showed that both deterministic processes and network modularity increased over time during the digestion process. It was concluded that the increase in temperature-mediated network modularity and deterministic processes on shaping the microbial interactions improved the stability and efficiency of anaerobic digestion process.
Keywords: Anaerobiosis; Microbial interactions; Modularity; Methane; bioreaktory; anaerobióza; Anaerobic digestion; Deterministic process; Temperature gradient; Bioreactors; Microbial Interactions; Temperature; mikrobiální interakce; methan; teplota